Innovations Applied in the Educational Process and their Specific Aspects (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article examines the application of educational innovations in the system of continuing education, as well as the types of innovation, the classification of innovations by scientists, aspects of evaluating pedagogical innovations, the stages of introducing educational innovations into the pedagogical process, the essence of innovative activity of teachers.